On Hermite–Hadamard-Type Inequalities for Coordinated h-Convex Interval-Valued Functions - Dafang Zhao; Guohui Zhao; Guoju Ye; Wei Liu; Silvestru Sever Dragomir (Mathematics, 2021)
This paper is devoted to establishing some Hermite–Hadamard-type inequalities for interval-valued functions using the coordinated h-convexity, which is more general than classical convex functions. We also discuss the relationship between coordinated h-convexity and h-convexity. Furthermore, we introduce the concepts of minimum expansion and maximum contraction of interval sequences. Based on these two new concepts, we establish some new Hermite–Hadamard-type inequalities, which generalize some known results in the literature. Additionally, some examples are given to illustrate our results.